2013
DOI: 10.1007/s10329-013-0391-1
|View full text |Cite
|
Sign up to set email alerts
|

Cathemerality in wild ring-tailed lemurs (Lemur catta) in the spiny forest of Tsimanampetsotsa National Park: camera trap data and preliminary behavioral observations

Abstract: Cathemerality consists of discrete periods of activity during both the day and night. Though uncommon within Primates, cathemerality is prevalent in some lemur genera, such as Eulemur, Hapalemur, and Prolemur. Several researchers have also reported nighttime activity in Lemur catta, yet these lemurs are generally considered "strictly diurnal". We used behavioral observations and camera traps to examine cathemerality of L. catta at the Tsimanampetsotsa National Park, Madagascar. Nighttime activity occurred thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
28
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 43 publications
3
28
0
2
Order By: Relevance
“…Studies from other non-gallery forest sites report large ring-tailed lemur group sizes without accompanying increases in Tamarindus density. Group sizes of >15 individuals (adults and subadults) inhabit the mixed deciduous/spiny bush forest of Tsimanampesotse National Park where Tamarindus has a limited distribution [LaFleur et al, 2014], and groups of 11-15 individuals occur in the far south in Cap Sainte-Marie where there is no tamarind [Kelley, 2013]. We also observed other large groups of ring-tailed lemurs on top of the escarpment while following our primary study group.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Studies from other non-gallery forest sites report large ring-tailed lemur group sizes without accompanying increases in Tamarindus density. Group sizes of >15 individuals (adults and subadults) inhabit the mixed deciduous/spiny bush forest of Tsimanampesotse National Park where Tamarindus has a limited distribution [LaFleur et al, 2014], and groups of 11-15 individuals occur in the far south in Cap Sainte-Marie where there is no tamarind [Kelley, 2013]. We also observed other large groups of ring-tailed lemurs on top of the escarpment while following our primary study group.…”
Section: Discussionmentioning
confidence: 56%
“…The tamarind fruits in these forests constitute the major food item annually for the lemurs, yet Tamarindus may be an exotic species to Madagascar, and reliance on its fruit may be of recent origin [Sauther and Cuozzo, 2009]. More recent surveys and field studies of populations from high altitudes to spiny desert scrub have broadened our understanding of what constitutes 'normal' conditions for ring-tailed lemurs [Goodman and Langrand, 1996;Gould et al, 2011;Kelley, 2013;LaFleur et al, 2014]. These sites typically have little to no tamarind trees, yet support sizable ring-tailed lemur populations.…”
Section: Introductionmentioning
confidence: 99%
“…See table 1 for study dates and the number of focal animal hours collected. Detailed data collection methods used for each study can be found in Gould et al [2011], Kelley [2013] and LaFleur et al [2013]. All plant food items consumed by each focal animal were recorded, as well as time spent feeding on each plant food, and plant food species were identified (1) via a herbarium at the Berenty field site, (2) at Missouri Botanical Gardens, St. Louis, for CSM plants, and (3) by botanist Bakira Ravorona for TNP plants.…”
Section: Data Collection and Analysismentioning
confidence: 99%
“…霊長類学における活動パターン研究の意義 現生の霊長類の活動パターンを分類群ごとに整理し ていくと,キツネザル下目を除く曲鼻猿亜目,すなわ ちロリス下目は夜行性であり,直鼻猿亜目はメガネザ ル下目と広鼻猿下目のヨザル属(Aotus)以外は昼行性 である (Griffin et al, 2012;Santini et al, 2015) 。霊長類 の共通祖先は夜行性であり,霊長類全体における進化 の流れとしては,夜行性から昼行性へと移行してきた と 考 え ら れ て い る (Griffin et al, 2012;Santini et al, 2015) 。霊長類における昼行性化は,群れや複雑な社会 性の進化を伴い (Shultz et al, 2011) ,視覚や脳の発達に もつながる一大イベントであったと考えられる (Barton, 1998) 。よって,霊長類における活動パターンの進化は 霊 長 類 学 の メ イ ン ト ピ ッ ク の ひ と つ に な っ て き た (Heesy & Ross, 2001;Martin, 1990;Martin et al, 2003) (Tattersall, 1979) 。やはり夜行性とも昼行 性とも適用しがたかったために,Tattersall(1987はギ リシャ語の"Kata(= Through) " と"Hemera(= Day) " を用いて"Cathemerality"という言葉を考案し,今日ま で使用されている。日本語では小山・高畑 ( 33:3 − 20, 2017(doi:10.2354 / psj.33.003) (Tattersall, 1987) Fernandez-Duque, 2003;A. trivirgatus Wright, 1989) 。曲鼻 猿亜目では既述の 3 属だけでなく,近年ではジェント ルキツネザル属に近縁なオオジェントルキツネザル属 (Prolemur)が周日行性に位置づけられた (Curtis, 2006;Curtis & Rasmussen, 2006) 。さらに,厳格な昼行性であ ると定義されていたワオキツネザル(Lemur catta)でも 夜間活動が確認されおり (Donati et al, 2013;LaFleur et al, 2014;Parga, 2011) Curtis et al, 1999;Rasmussen, 1999Rasmussen, , 2005Tattersall, 1987) (Rasmussen, 1999(Rasmussen, , 2005Tarnaud, 2006) 。雨季と乾季が明瞭な熱帯乾燥林に みられる。 C タイプ:1 年を通して昼も夜も活動する恒常的な周日 行性を示す (Colquhoun, 1998;Donati & Borgognini-Tarli, 2006;Schwitzer et al, 2007a) 。季節が不明瞭な熱帯雨林 にみられる。 これらの共通点や差異を生じさせる至近要因と究極 要因については,後ほど触れていく。 2. 周日行性は昼行性化の途中か? 霊長類の共通祖先が夜行性であることは長らく主張 されており,近年の研究においても強く支持されてい る (Griffin et al, 2012;Santini et al, 2015) 。我々ヒトを 含め,直鼻猿亜目のほとんどは昼行性であることから, 霊長類は夜行性から昼行性に進化してきたといえる (Santini et al, 2015) 。一方,原始的...…”
unclassified
“…周日行性は昼行性化の途中か? 霊長類の共通祖先が夜行性であることは長らく主張 されており,近年の研究においても強く支持されてい る (Griffin et al, 2012;Santini et al, 2015) 。我々ヒトを 含め,直鼻猿亜目のほとんどは昼行性であることから, 霊長類は夜行性から昼行性に進化してきたといえる (Santini et al, 2015) 。一方,原始的な霊長類の特徴を多 く残すキツネザル下目において夜行性・周日行性・昼 行性の種が混在していることから, 「周日行性はもとも と夜行性だった種による昼行性化の途中であり,進化 的に不均衡な状態なのか?」それとも「周日行性は適 応進化した完成型なのか?」という問いかけがなされ てきた。本節では近年になって終結しつつある,系統 発生上の論争をまとめていきたい。 2.1. 進化的不均衡仮説 マダガスカル島では 2300-1200 年ほど前にヒトが移入 して以降 (Cox et al, 2012;Tofanelli et al, 2009) ,それま で日中の生態的ニッチを独占していた現生キツネザル の競争相手となりうるジャイアントリーマー[8 属から 成り体重 10-200 kg もあったとされる大型キツネザル類 の 総 称 Jungers et al, 2002) Goodman 1994;Goodman & Muldoon, 2016)が狩猟によって絶滅したとされている (Goodman & Jungers, 2014) (Griffin et al, 2012;Santini et al, 2015) (Eppley et al, 2015)やワオキツネ ザ ル 属 (Donati et al, 2013;LaFleur et al, 2014;Parga, 2011)における周日行性の位置づけは 2010 年代に入っ てからである。さらに近年の系統解析ではキツネザル 下目の共通祖先の主要分岐群からまずキツネザル科が, 次にインドリ科が独立に分岐したと考えられている (Horvath et al, 2008) 。これらの新しいデータを用いて 各活動パターンの起源を探った Santini et al(2015)は, キツネザル科の共通祖先で夜行性から周日行性が進化 し,インドリ科ではアバヒ属(Avahi)を除くインドリ 属(Indri)およびシファカ属(Propithecus)それぞれの 共通祖先で夜行性から昼行性が進化したと結論づけて いる(図 2b) 。キツネザル科の中で現在もエリマキキツ ネザル属だけが昼行性の扱いとなっているが (Santini et al, 2015) ,エリマキキツネザル属では夜間活動の研究 が乏しく,今後の研究次第で周日行性への位置づけの 可能性は十分にあり得るという (Donati et al, 2013) 。 よっ て周日行性の起源はキツネザル科の共通祖先が出現し た 4600-2000 万年前まで遡ることになる (Donati et al, 2013;Santini et al, 2015) 。 Griffin et al(2012 にしても Santini et al(2015) (Jacobs et al, 1996) (Jacobs & Deegan, 2003;Surridge et al, 2003;Tan & Li, 1999;Veilleux & Bolnick, 2009 (Bearder et al, 2006;Kirk, 2006;Santini et al, 2015) 。よって,目の構造および機能の検証からも進化 的不均衡仮説は否定されるのである。 一方で現在みられる活動パターンと一致していな...…”
unclassified